The Influence of Talent Management Development, Recruitment, and Competence on Employee Performance Through Job Training - Himawan, Muhammad Reza; Yulasmi, Yulasmi; Yenni, Zefri (UPI YPTK Journal of Business and Economics, 2024)
This research focuses on the employee performance of the Sungai Penuh City Government. The study adopts a quantitative causality approach, using data collected through questionnaires. The analysis was conducted using multiple linear regression techniques with the SmartPLS program, and a saturated sample of 50 respondents was used for the study. The results indicate that talent management has a positive and significant effect on job training, and recruitment also shows a positive and significant impact on job training. However, competency does not significantly affect job training. Furthermore, talent management has a positive and significant effect on employee performance, while recruitment and competency do not significantly influence employee performance. Additionally, job training itself does not significantly impact employee performance. It is also concluded that job training does not mediate the relationship between talent management and employee performance. However, job training mediates the effects of recruitment and competency on employee performance.